Bioprospecção de moléculas tensoativas em fungos endofíticos de Piper hispidum e Myrcia guianensis. - Silva, Messe Elmer Torres da (2015)
Fungi found in plant species, called endophytic fungi, present a great potential for the production of new bioactive substances. Among substances of commercial interest are the biosurfactants, compounds that present tensoactive properties and are produced by microorganisms. Biosurfactants comprise a wide variety of applications, which include bioremediation, biodegradation, cleaning of oil containers, and are also employed at the food, pharmaceutical and cosmetic industries. Therefore, this work has evaluated the biosurfactant production on metabolic broths of endophytic fungi isolated from Amazon species Piper hispidum and Myrcia guianensis. In order to access the biosurfactant production it was carried out the drop collapsed test and the determination of the emulsification index (E24). Biosurfactant physical-chemical properties, such as the lowering of superficial tension (ST) and the critical micelle concentration (CMC) were determined in order to verify its efficiency. 117 endophytic fungi were isolated from P. hispidum and 50 were used for the production of tensoactive molecules. Of these, eight presented positive results at the drop collapsed test and E24 varied from 20 to 78%. It was selected 32 M. guianensis endophytic fungi from the Laboratory of Chemistry Applied to Technology (EST/UEA). Of these, 12 presented positive results at the drop collapsed test and E24 varied from 60 to 75%. Considering the best results, fungi were cultivated in 1L media for biosurfactant extraction and physical-chemical properties evaluation. Biosurfactant recovering was performed using cold ethanol and promoted a 2.46 to 4.47 g/L of tensoactive molecules. ST lowering and CMC values were only verified for the metabolic broths of the four fungi that presented the best results of emulsification index: MgRe 1.3.3; MgC 3.3.2; Ph II 22G and Ph III 23F. The metabolic media that presented the greater ST lowering (37%) was the one of M. guianensis isolate MgRe 1.3.3 (identified as Colletotrichum gloeosporioides), which reduced ST from 61.0 to 39 mN.m-1. The lowest CMC value was also found for this isolate, of 4.6 mg.mL-1. Other two fungi strains were identified using molecular biology techniques. MgC 3.3.2 was identified as Aspergillus niger and Ph II 22G as Glomerella cingulata. Considering these results, it was possible to access P. hispidum and M. guianensis endophytic fungi that produce biosurfactants which presented promising physical-chemical properties for being used in different industrial areas. Keywords: Biosurfactant, Endophytic fungi, P. hispidum, M. guianensis.